Early human settlement and natural formation of the Florida Everglades, USA: The Ichthyoarchaeological evidence. (August 2016) - Fradkin, Arlene
Abstract: The Everglades, the largest subtropical wetland in North America, was initially formed by natural processes approximately 5000 years ago and has since dominated the interior landscape of south Florida. Scattered throughout this vast freshwater marsh are tree islands, small clusters of trees situated on slightly elevated ground, which stand out conspicuously amid the surrounding lower vegetation. As the only dry land available, tree islands were ideal for human settlements in the distant past and contain numerous archeological sites. Recent excavations at several sites lend further support to existing evidence that human populations had initially camped on these interior tree islands quite early in time. One such site is Heartleaf Hammock, where rich well-preserved midden deposits demonstrate that people intensively occupied and used locally available aquatic resources, especially fish, as early as 4400 years ago. Moreover, the kinds and relative quantities of fish and other freshwater fauna represented indicate that the Everglades wetland marsh ecosystem was already in existence at the time of this early human occupation. Highlights: Fish remains are examined from a Florida Everglades tree island archaeological site. The site represents one of the earliest evidence for human presence in the Everglades. Fish and other aquatic fauna identified indicate the Everglades existed at the time of this early human occupation.